Technoeconomic evaluation of flared natural gas reduction and energy recovery using gas-to-wire scheme - Anosike, Nnamdi Benedict (Cranfield University, 2013)
Most mature oil reservoirs or fields tend to perform below expectations, owing to high level of associated gas production. This creates a sub-optimal performance of the oil production surface facilities; increasing oil production specific operating cost. In many scenarios oil companies flare/vent this gas. In addition to oil production constraints, associated gas flaring and venting consists an environmental disasters and economic waste. Significant steps are now being devised to utilise associated gas using different exploitation techniques. Most of the technologies requires large associated gas throughput. However, small-scale associated gas resources and non-associated natural gas reserves (commonly referred to as stranded gas or marginal field) remains largely unexploited. Thus, the objective of this thesis is to evaluate techno- economic of gas turbine engines for onsite electric power generation called gas- to-wire (GTW) using the small-scaled associated gas resources. The range of stranded flared associated gas and non-associated gas reserves considered is around 10 billion to 1 trillion standard cubic feet undergoing production decline. The gas turbine engines considered for power plant in this study are based on simple cycle or combustion turbines. Simple cycle choice of power-plant is conceived to meet certain flexibility in power plant capacity factor and availability during production decline. In addition, it represents the basic power plant module cable of being developed into other power plant types in future to meet different local energy requirements. This study developed a novel gas-to-wire techno-economic and risk analysis framework, with capability for probabilistic uncertainty analysis using Monte Carlo simulation (MCS) method. It comprises an iterative calculation of the probabilistic recoverable reserves with decline module and power plant thermodynamic performance module enabled by Turbomatch (an in-house code) and Gas Turb® software coupled with economic risk modules with @Risk® commercial software. This algorithm is a useful tool for simulating the interaction between disrupted gas production profiles induced by production decline and its effect on power plant techno-economic performance over associated gas utilization economic life. Furthermore, a divestment and make- up fuel protocol is proposed for management of gas turbine engine units to mitigate economical underperformance of power plant regime experienced due to production decline. The results show that utilization of associated gas for onsite power generation is a promising technology for converting waste to energy. Though, associated gas composition can be significant to gas turbine performance but a typical Nigerian associated gas considered is as good as a regular natural gas. The majority of capital investment risk is associated with production decline both natural and manmade. Finally, the rate of capital investment returns decreases with smaller reserves.
Keywords: small-scaled flared associated gas utilization; combustion gas turbines; onsite power generation; associated gas production decline; power plant operations alternatives; gas turbines unit divestment; makeup –fuel; uncertainty analysis